Intention to use the deliver eat online food delivery app in Malaysia, a behavioral study among gen - Chew, Yi Wei (2023)
This study focus on the use and uptake of mobile food delivery apps in Malaysia. With the rising trend of utilizing mobile apps to order meals, it is critical to identify the elements that drive such app adoption in Malaysia. The majority of millennials (those born between 1968 and 2006) are employees and students. They have spending power and are eager to employ the OFD service if it saves them time and effort. The outcomes of this study will emphasize the importance of identifying the IVs that influence mobile app usage intentions. Deliver Eat decision-makers may discover issues that can restrict or promote the implementation of mobile technology in their firm by studying these characteristics. In this research, it is examining the effects of IVs: MAU; sub-variables of MAEU: compatibility and SE; and MAI to the intention to use Deliver Eat online mobile food app. The conceptual framework of this study is modified based on the MTAM by decomposing the MAEU into two sub-variables and one additional variable. 394 responses are collected from the online questionnaires where 10 are voided and the remaining are used as the analysis data in this study. The snowball sampling approach was applied in distributing the questionnaire, which used a 5-point Likert scale for assessing the variables' items. The regression results indicated the variables MAU, compatibility, and MAI are substantially associated to the intention to use Deliver Eat online mobile food app. In discussing the reason of each hypothesis is accepted or not supported, reasonable explanations and solutions are presented. Strategic methods are proposed by referring to the significant predictors' measurable items. The project's shortcomings and recommendations for future studies have also been explored.